Blood RNA biomarkers and a point-of-care elastase assay for detecting host immune activation in suspected sepsis: Trajectory matters - John E. Lafleur; Eduard Shaykhinurov; John Perkins; Richard Wargowsky; Kevin Jaatinen; Mary Pasquale; Grace Holloway; David Yamane; Akhil Patel; Daniel King; Andrew Meltzer; Ryan Heidish; et al. (PLoS ONE, 2025)
Introduction/Hypothesis The chances of survival from sepsis are improved by early diagnosis and treatment. In the prospective SENSOR study, RNA biomarkers of innate immune neutrophil activation were examined in emergency department (ED) patients triggering an automated sepsis alert. We hypothesized that higher levels of blood RNA biomarkers related to neutrophil activation would be associated with progression to more severe forms of sepsis. Methods Adult patients in the ED triggering a sepsis alert were consented, enrolled, and study samples were obtained during the ED visit. Additionally, study samples were collected from a convenience sample of 16 adult non-ED controls and 8 other adults with self-described infectious illnesses. Blood samples were drawn in RNA preservative (Tempus) and whole blood RNA was analyzed by droplet digital PCR (ddPCR) for RNA transcripts related to neutrophil response to infection by bacterial (DEFA1; ALPL, IL8RB/CXCR2), and viral (IFI27, RSAD2) pathogens. Bacterial burden in blood was quantitated by ddPCR of 16S ribosomal DNA. Separately, neutrophil elastase was measured in immunomagnetically captured CD66b+ neutrophils by a novel point-of-care device. Results Patients were grouped using both ‘Sepsis-2’ SIRS criteria, adjudicated by independent physicians, and ‘Sepsis-3’ criteria which uses a qSOFA score for categorizing the severity of illness. Across 72 enrolled sepsis alert patients, 62.5% showed positive RNA biomarkers for bacterial infection, and 8.3% were positive for viral markers, with only 2 cases that showed only a viral signal. Septic patients showed a 4-fold increase in RNA markers vs. those without infection (p < 0.05). However, no significant differences were observed in RNA levels between those with sepsis vs those with more severe forms of sepsis. Likewise, RNA biomarker levels did not discriminate patients with qSOFA≥2 from qSOFA = 1. In a subset of patients with zero and three hour blood samples (n = 27) it was found that changes in RNA levels (up or down), or neutrophil elastase activity, was strongly associated with progression to more severe forms of sepsis or a qSOFA score of ≥2. Conclusions Patients progressing to more severe forms of sepsis did not have higher absolute levels of neutrophil activation RNA biomarkers (or higher bacterial burden in blood) compared to patients with sepsis. However, a change in RNA biomarkers or elastase between zero and three hours was strongly indicative of progression to more severe forms of sepsis.